Perancangan Laboratorium Komputer Virtual Mandiri Untuk Praktikum Jaringan Komputer Dasar Menggunakan Docker - Iman Aidil Nugraha; Mahendra Data; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Laboratory is a means to conduct the process of practicum at a university. The purpose of a practicum is held so that students can directly implement the material obtained at the time the lectures take place in the classroom. However, when practicum there are students who are difficult to perform the installation of practical purposes, it is caused by the uniformity of configuration requirement of practicum between lecturer and student. To overcome these problems it takes a virtual laboratory to do a practicum. This virtual laboratory serves as a lab that can be accessed virtually on each student device. In this study used the docker engine as a virtualization software provider. Practicum used as virtualization is a computer network practice module that each chapter will be used as an image using docker. Furthermore, to run the lab can be through the container provided by the docker. Docker is chosen because the use of memory, processor and storage are more efficient. Tests conducted in this study is a test of computer performance, which is seen from memory usage and CPU usage. the test performed resulted in the use of memory of 1.21MB and 0.7% of CPU usage on packet capturing practice, 6.77MB and 0.6% CPU usage on socket programming practice, 2.30MB and 2.93% CPU usage on protocol layer transport pratice.